Caffeine Attenuates Electroacupuncture Effect on Pressure Pain Threshold and Tolerance in Healthy Individuals: A Randomized Controlled Trial - Liu, Kun; Cui, Xiang; Zhi, Mujun; Zhang, Meng; Zhao, Ting; Gao, Xinyan; Zhu, Bing (Frontiers in Neurology, 2022)
Introduction: The effect of caffeine on acupuncture analgesia in humans is unclear. This study aimed to investigate whether caffeine-containing beverage intake influence the effect of electroacupuncture (EA) on static quantitative sensory testing (QST) and dynamic QST in healthy subjects. Methods: Forty healthy subjects were enrolled and randomly assigned to receive coffee containing moderate doses of caffeine (coffee group) or noncaffeinated juice (juice group) for 4 weeks. The primary outcome measures were the pressure pain threshold (PPT), pressure pain tolerance (PPTo) and heat pain threshold (HPT) as static QST parameters. Numerical rating scales (NRS) of heat stimulus and nociceptive flexor reflex (RⅢ reflex), as parameters of dynamic QST, were also examined. EA stimulation with tolerance intensity was performed at ST36 (Zusanli) - GB34 (Yanglingquan) points at weeks 0, 2, and 4. PPT, PPTo, and HPT were detected pre- and post- EA, and NRS scores were examined pre-, during, and post- EA and 1min after EA was completed. The RIII reflex was examined pre-, and 1-5 min post-EA. Results: At week 0, both groups showed increased PPT and PPTo and decreased NRS scores of heat stimulus and RIII reflex after EA, but HPT was not affected. After 4 weeks, the effects of EA on PPT and PPTo were attenuated in the coffee group compared to the juice group, whereas the effect of EA on the NRS scores and RⅢ reflex were not influenced. There was no significant difference found at week 2 for these indications. EA also did not affect the HPT in both groups at week 4. Conclusion: Moderate caffeine intake reduced the effects of EA on PPT, PPTo in healthy subjects. Keywords: coffee, electroacupuncture, quantitative sensory testing, sensory perception, conditioned pain modulation